2021
DOI: 10.1017/sjp.2021.9
|View full text |Cite
|
Sign up to set email alerts
|

Role Salience and the Growth Intention of Women Entrepreneurs: Does Work-life Balance Make a Difference?

Abstract: Work and family are two of the most competing and salient roles in the life of every individual. As such, individuals often make behavioral decisions based on the relative salience (work or family) they attach to these life roles. Given that growth intention is a vital behavioral choice in the life of an entrepreneur, this study examined how role salience influences the growth intentions of women entrepreneurs. Moreover, for most women entrepreneurs, their family domain is highly entwined with the business dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Furthermore, the data demonstrated that job choice is no longer exclusive to the male members of the family but that females have also begun opting out of the same fields. However, the support of their families is equally vital to them, and they want to have it so that they can continue to meet the growing demands of business [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the data demonstrated that job choice is no longer exclusive to the male members of the family but that females have also begun opting out of the same fields. However, the support of their families is equally vital to them, and they want to have it so that they can continue to meet the growing demands of business [8][9][10].…”
Section: Resultsmentioning
confidence: 99%
“…Work balance is a factor that positively influences job outcomes like job performance, and employee well-being is affected by work-life balance (Carlson et al, 2009). Work-family balance positively influences employee performance and growth (Zhang et al, 2019;Neneh, 2021).…”
Section: Work-family Balance and Job Outcomesmentioning
confidence: 99%